The Use of Writeabout.Com as a Platform to Teach Writing in Senior High School - Dina Ulfa Desta Safda; Refnaldi Refnaldi (Universitas Negeri Padang, 2019)
The teacher can use writeabout.com to teach writing to engage students to write more since good writing has long process and needs a lot of practice. By applying this method, the teacher can use Writeabout.com, a website that can help students to improve their writing skill. The use of Writeabout.com can help students have a more interesting way to write and to solve students’ problems.Most problems students have is getting idea, so this website can help by providing thousands ideas for writing starter. It can be applied for senior high school students because most of them have android to access this website. The objective of this paper is to help the teacher find new technique in order to increase students’ interest to write.Throughwriteabout.com, the students can upload their writing and get responses from some people and even native, and they can get new friends in website. In sum, there are many advantages that can students find by learning through writeabout.com.